Physicochemical and textural properties of squid (Loligo vulgaris) muscle treated with organic acids - Gokoglu, Nalan (Acta Aquatica: Aquatic Sciences Journal, 2023)
The aim of this study is to investigate the effects of organic acid treatments on tenderizing of squid muscle. Squid samples removed head, skin, viscera, and tentacles and cut into square pieces of 4 x4 cm were soaked into the citric and lactic acid solvents (1 and 2%) and kept in a refrigerator (4°C) for 24 h. It was found that organic acid treatments affected the physicochemical properties of squid. While acid application decreased pH values and water holding capacity, its increased cooking loss and free amino acid content. Texture profile parameters and sensory texture scores did not change significantly after acid treatments. The type and concentration of acids were not effective for all parameters except cooking loss.Keywords: Physicochemical; Organic acids; Squid; Texture